The use of molecular typing for characterization of a Salmonella Enteritidis cluster - Silveira, Leonor (2018)
Although the number of Salmonella Enteritidis has been declining in Europe in recent years due to successful control measures implemented in poultry industry, it remains the most commonly detected serovar of human non-typhoidal salmonellosis. Here, we reported the first Salmonella Enteritidis outbreak investigated by the Portuguese Reference Laboratory for Salmonella where traditional typing data was reinforced by Whole Genome Sequencing (WGS) data. In July 2016 the National Reference Laboratory for Gastrointestinal Diseases of the National Institute of Health Doutor Ricardo Jorge received 10 strains of Salmonella from a suspected human outbreak in Lisbon and Tagus Valley region. Serotyping was performed according to Kauffman-White-Le Minor scheme and antimicrobial susceptibility was tested according to EUCAST recommendations. Isolates were characterized by Multilocus Sequence Typing (MLST), Multiple-Locus Variable number tandem repeat Analysis (MLVA) and WGS. All strains were identified as S. Enteritidis ST11. Nine of them had the MLVA profile 3-11-5-4-1 and another strain had a rather different MLVA profile (2-10-9-2-2). This strain had also a different antibiotic resistance profile (being resistant only to sulphametoxazole while related MLVA 3-11-5-4-1 strains were resistant only to nalidixic acid), which reinforces that this isolate is very likely not associated with the outbreak. WGS analysis of four outbreak-related strains confirmed that these strains share the same serotype (Enteritidis) and MLST profile (ST11), allowed the in silico prediction of the same ribotype (rST 1425), and confirmed the genetic relatedness at whole-genome level. Unfortunately, no strains from any potential food sources were obtained. MLVA is traditionally used for Salmonella Enteritidis surveillance in Europe, since it is a rapid and reproducible high-resolution typing technique that allows detection of national and multinational outbreaks. However, WGS is progressively replacing the traditional geno- and phenotyping techniques for routine surveillance and outbreak investigation. This report is a good example not only that WGS provides an optimal discriminatory power for outbreak resolution, but also that allows performing several subtyping tests (ST determination, in silico serotyping and ribotyping) from a single assay.